CASE OF A GIANT MYOMA NODE BIRTH AFTER UTERINE ARTERIES EMBOLIZATION - Эльвира Константиновна Гребенникова; Виталий Борисович Цхай; Валентина Сергеевна Гладкая; Ирина Сергеевна Брехова; Сергей Михайлович Брюховец; Марина Яковлевна Домрачева; Галина Николаевна Полстяная; Вячеслав Николаевич Коновалов (The Publishing House Medicine and Enlightenment, 2019)
Uterine artery embolization (UAE) is currently widely used in gynecological practice and is an alternative to hysterectomy in women with symptomatic uterine myoma. The decision to perform UAE in women with large and giant uterine fibroids is, in most cases, extremely difficult due to the potential risk of serious postoperative complications. This article presents the case of a favorable outcome after the EMA in a 45 year-patient with the giant myoma node who refused to have surgery and hysterectomy.